Diversity analysis of bacterial community in acid saline ‘Pokkali’ soil of Kerala through metagenomic approach - Sah, Sarveshwar; Girija, D; Deepa, K; A, Nazeem P; M, Firoz P; E, Sunil (Journal of Tropical Agriculture, 2014)
Diversity of bacterial community in acid saline Pokkali soil from Vyttila, Kerala was analyzed through metagenomic approach. Environmental DNA was isolated from soil by direct extraction. The gene encoding 16S rRNA component of 30S subunit of prokaryotic ribosome was used as barcode for bacterial identification. 1500bp fragment of 16S rDNA was amplified by polymerase chain reaction. Amplicons were ligated in plasmid vector pGEMT and cloned in E. coli. Sequence analysis of 30 randomly picked clones from the metagenomic library revealed that 23 clones (76.7%) were of unculturable bacteria. The most predominant phylum was Proteobacteria, which included Ectothiorhodospiraceae, Azospira sp., Stenotrophomonas maltophilia, Thiobacillus prosperus, Levilinea saccharolytica, Desulfobacteraceae, Thioalkalivibrio sp. and Rhodocylales. Other phyla included Chloroflexi, Acidobacteria and Cyanobacteria. A diverse group of bacteria including acidophiles, halophiles, denitrifiers, S oxidizers, sulphate reducers, aerobes, strict anaerobes, thermophiles, mesophiles and photosynthetic bacteria were detected. Six clones of the unculturable bacteria shared homology with no sequence in NCBI database, indicating that these could be novel. Phylogenetic tree based on partial 16S rRNA gene placed 30 clones in three major clusters- Proteobacteria, Chloroflexi and Acidobacteria. Metagenomic approach successfully revealed the composition and diversity of bacterial community inPokkali soil.